2014
DOI: 10.1002/2013wr014292
|View full text |Cite
|
Sign up to set email alerts
|

With or against the tide: The influence of bed form asymmetry on the formation of macroturbulence and suspended sediment patterns

Abstract: This study examines tide-dependent variations in the formation and dynamics of suspended sediment patterns coupled to mean flow and turbulence above asymmetric bed forms. In the Danish Knudedyb inlet, very large primary bed forms remain ebb-oriented during a tidal cycle while smaller superimposed bed forms reverse direction with each tidal phase. Hydroacoustic in situ observations reveal pronounced differences in suspended sediment transport patterns between tidal phases caused by the relative orientation of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…These observations were in agreement with the basics on dynamics of the ocean circular vortex and wave motions [17,18]. Tide-dependent variations in the formation and dynamics of suspended sediment patterns coupled to mean flow and turbulence above asymmetric bedforms were examined [19]. A decrease in water clarity of the southern and central North Sea was reported [20].…”
supporting
confidence: 82%
See 1 more Smart Citation
“…These observations were in agreement with the basics on dynamics of the ocean circular vortex and wave motions [17,18]. Tide-dependent variations in the formation and dynamics of suspended sediment patterns coupled to mean flow and turbulence above asymmetric bedforms were examined [19]. A decrease in water clarity of the southern and central North Sea was reported [20].…”
supporting
confidence: 82%
“…As a first approximation, roughness effects were neglected for simulations of the different hydrodynamic parameters according to Eqs. (1)- (19). This is a crucial point in the theory because the lift and downforce coefficients were derived by using a flat plate.…”
Section: Discussionmentioning
confidence: 99%
“…These landers bridge the observational gap between longterm monitoring stations, remote sensing applications, and ship-based field campaigns. They are mobile, and can be used to spatially interpolate between monitoring stations and provide data with very high temporal resolution (Kwoll et al, 2013(Kwoll et al, , 2014Oehler et al, 2015a;Ahmerkamp et al, 2017). Lander operations aim at measuring various processes close to the seafloor or in the sediment and are designed to have minimal impact on the environment and quantities that are measured.…”
Section: Landersmentioning
confidence: 99%
“…During some parts of the tidal cycle a periodic stratification of the water column has been observed in shallow areas of the German Bight forming distinct layers that move independently with a decoupled tidal ellipticity (KrĂ€mer and Winter, 2016;Kwoll et al, 2013Kwoll et al, , 2014Ahmerkap et al, 2017). The difference in sea bed dynamics between fair weather conditions and storms is also investigated in the research area "Seafloor Dynamics" of the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) Research Center/Cluster of Excellence "The Ocean in the Earth System".…”
Section: Lander Sedobsmentioning
confidence: 99%
“…These observations have shown that the larger dunes remain oriented towards and slowly migrate in the direction of the dominant tidal flow, whereas surveys taken during maximum ebb and flood reveal smaller bedforms reverse asymmetry with the tides (Bokuniewicz et al, 1976;Winter et al, 2008;Kwoll et al, 2014). Although these studies provide accurate maps of the bedforms and information of their asymmetry and long timescale migration, they lack detail on bedform dynamics throughout the tidal cycle.…”
mentioning
confidence: 99%